Discrete Mathematical Structures - Kolman, Bernard, 1932- ; Busby, Robert C. and Ross, Sharon Cutler, 1943- (Noida, India Pearson Education, 2016)
Originally published in 2009, reissued as part of Pearson's modern classic series
Include Glossary and Index
Keywords: Computer science--Mathematics